Pembangunan Web Server Mengunakan Debian Server Untuk Media Pembelajaran Di Sekolah Menengah Kejuruan (SMK) Negeri 1 Sragen - Indrat Susilo; Gesang Kristianto Nugroho (Indonesian Journal of Networking and Security (IJNS), 2013)
ABSTRACT – Along with the development of more advanced technology that affects a system and operational efficiency in the field work in the life, many educational institutions that use computer networks and internet facilities to support teaching and learning process. By using a network of computers and internet facilities, teachers and students can find references of learning and easyy to communicate in order to support the learning process. The aim of this study is  to generate a web server in the Vocational School SMK N  1 Sragen as website for student learning. The advantage of this research to increase student learning that supported by the media website and find out how technical implementation of a network client - server in the Vocational School SMK N 1 Sragen. The methods that the writer used are literary method, observation, interviews, analysis, design, testing, and implementation. In the design and manufacture of web server, the writer uses the debian squeeze 6. The results of this study are to optimize the network of Local Area Network (LAN) as a medium of learning for the benefit of education. Keyword : Web Server   Abstraksi – Seiring dengan perkembangan teknologi yang semakin maju mempengaruhi suatu sistem dan efisiensi operasional dalam dunia kerja di bidang kehidupan, banyak instansi pendidikan yang menggunakan fasilitas jaringan komputer dan internet untuk mendukung proses belajar mengajar. Dengan memanfaatkan jaringan komputer dan fasilitas internet, guru dan siswa dapat mencari referensi pembelajaran dan kemudahan komunikasi demi mendukung proses pembelajaran. Penelitian ini bertujuan untuk Menghasilkan web server pada Sekolah Menengah Kejuruan Negeri 1 Sragen sebagai website pembelajaran siswa. Penelitian ini bermanfaat untuk Meningkatkan pembelajaran siswa yang didukung dengan media website serta mengetahui cara teknik implementasi suatu jaringan client – server di Sekolah Menengah Kejuruan Negeri Negeri 1 Sragen. Metode yang penulis gunakan adalah metode studi pustaka, observasi, wawancara, analisis, perancangan, uji coba, implementasi. Dalam perancangan dan pembuatan web server ini penulis menggunakan debian squeeze 6. Hasil dari penelitian ini adalah mengoptimalkan jaringan Local Area Network (LAN) sebagai media pembelajaran. Kata Kunci : Web Server